Estimation of the outcrossing rate for annual Asian wild rice under field conditions - Phan, Phuong Dang Thai (Japanese Society of Breeding, 2012)
The Asian wild rice, Oryza rufipogon, has partial outcrossing behavior and shows high levels of genetic variation. To estimate an accurate outcrossing rate of annual form of O. rufipogon, two backcross lines (Lines R1 and R2) between Oryza sativa Nipponbare and O. rufipogon W630 were examined under field conditions. A chromosome survey confirmed that these lines had wild chromosomal segments at more than 92% of marker loci. As for the traits of glume, stamen and pistil, Line R1 showed similar floral morphology as that of O. rufipogon W630, whereas Line R2 had larger glumes. In 2005, 2006 and 2008, a total of 22 backcross plants were planted in the middle of wild rice plots. The successive progenies of each plant were examined using microsatellite markers that could clearly detect self-pollination and outcrossing. The outcrossing rates of Line R1 plants ranged from 4.04% to 25.50% with an average of 10.20%. This indicates that cross-pollination of wild rice is a chance event affected by many environmental factors. The outcrossing rates of Line R2 plants also varied, however, no significant difference was observed between the averages of Lines R1 and R2, suggesting that the glume sizes are not critical for outcrossing ability.